2018
DOI: 10.20517/2574-1225.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal delivery outcomes in pregnancies following bariatric surgery: a meta-analysis of the literature

Abstract: Aim: The objective of this study is to evaluate maternal and fetal outcomes following pregnancies after bariatric surgery as compared to the general population affected by obesity. Methods:A systematic review was conducted through MEDLINE, Cochrane, and EMBASE to identify relevant studies from 2007 to 2016 with comparative data on the maternal and fetal delivery outcomes following bariatric surgery as compared to the population affected by obesity. The primary outcome analyzed was the rate of cesarean deliveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…In the comparison of pregnancies in women with a history of bariatric surgery with women having normal body mass index, a higher incidence of pregnancy complications has been observed. This is in contrast to when obese women were used as the control group, often no significant reduction in complications was reported [ 11 , 12 , 22 , 23 ]. Bariatric surgery may reduce the occurrence of obesity-related complications during pregnancy, but not to the same extent as in the population of women with normal weight [ 17 ].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the comparison of pregnancies in women with a history of bariatric surgery with women having normal body mass index, a higher incidence of pregnancy complications has been observed. This is in contrast to when obese women were used as the control group, often no significant reduction in complications was reported [ 11 , 12 , 22 , 23 ]. Bariatric surgery may reduce the occurrence of obesity-related complications during pregnancy, but not to the same extent as in the population of women with normal weight [ 17 ].…”
Section: Introductionmentioning
confidence: 89%
“…A meta-analysis showed lower rates of preeclampsia and gestational diabetes, but increased maternal anemia [ 24 ]. However, there was variation among the studies used in the meta-analysis on pregnancy-induced hypertension [ 23 ]. While most studies did not show any difference between the two groups with and without a history of surgery, one study showed a lower prevalence of hypertension in pregnant women who underwent bariatric surgery compared to pregnant women with obesity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nausea or vomiting during pregnancy may exacerbate the mother's poor nutritional status, and serious complications may occur unless adequate supplementation is taken (20). Studies on birth weight after bariatric surgery show a decrease in average birth weight and fetal macrosomia, and an increase in small for gestational age (SGA) fetuses and intrauterine growth restriction (IUGR) of infants (11,12,23). These trends are most likely caused by maternal malnutrition following bariatric surgery and micronutrient de ciency, which may be exacerbated during pregnancy (22).…”
Section: Maternal-fetal Outcomes In Pregnancy After Bariatric Surgerymentioning
confidence: 99%
“…Studies showed reduction in incidence of preeclampsia after bariatric surgery were many [ 26 , 31 , 32 , 33 ]. An increase in incidence of pregnancy induced hypertension was reported in meta-analysis involving 13 studies by Young B et al (2018) [ 34 ]. The increase in incidence could be attributed by older age group and white patients.…”
Section: Overview Of Bariatric Surgerymentioning
confidence: 99%